2022
DOI: 10.1080/2162402x.2022.2093518
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade synergizes with oxaliplatin-based, but not cisplatin-based, chemotherapy of gastric cancer

Abstract: Preclinical experimentation revealed that established cancers treated with the immunogenic cell death (ICD) inducer oxaliplatin are sensitized to immune checkpoint inhibitors targeting PD-1. In contrast, no such sensitizing effect is observed when cisplatin, a non-immunogenic cell death inducer is used. Two randomized phase III clinical trials targeting unresectable gastric and gastro-esophageal junction carcinomas apparently validate this observation. Thus, oxaliplatin-based chemotherapy (together with capeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…In a variety of rodent tumor models, ICD signaling has been mechanistically linked to superior responses to clinically relevant therapies, including (but not limited to) chemotherapy based on anthracycline and (some) platinum derivatives [ 63 , 64 ], targeted anticancer agents specific for epidermal growth factor receptor (EGFR) [ 19 ], multitarget tyrosine kinase inhibitors [ 65 ], radiation therapy [ 66 , 67 ], and photodynamic therapy [ 68 ]. Specifically, in numerous prophylactic or therapeutic experimental settings involving the aforementioned clinically relevant agents, pharmacological or genetic strategies interrupting stress signaling in cancer cells, DAMP emission therefrom, or DAMP detection by immune cells compromised the emergence of protective anticancer immunity or disease control, respectively [ 45 ].…”
Section: Icd and Cancer (Immuno)therapymentioning
confidence: 99%
“…In a variety of rodent tumor models, ICD signaling has been mechanistically linked to superior responses to clinically relevant therapies, including (but not limited to) chemotherapy based on anthracycline and (some) platinum derivatives [ 63 , 64 ], targeted anticancer agents specific for epidermal growth factor receptor (EGFR) [ 19 ], multitarget tyrosine kinase inhibitors [ 65 ], radiation therapy [ 66 , 67 ], and photodynamic therapy [ 68 ]. Specifically, in numerous prophylactic or therapeutic experimental settings involving the aforementioned clinically relevant agents, pharmacological or genetic strategies interrupting stress signaling in cancer cells, DAMP emission therefrom, or DAMP detection by immune cells compromised the emergence of protective anticancer immunity or disease control, respectively [ 45 ].…”
Section: Icd and Cancer (Immuno)therapymentioning
confidence: 99%
“…As a limitation of our approach, clinical validation for the therapeutic utility of our concept has only been obtained for ICD inducers in prospective clinical trials, 72–76,80 while most of the evidence is based on retrospective analyses 13,26,61–70 . Clinical evidence in favor of the use of T‐cell stimulators is based on retrospective observations and is merely correlative 86,90–94 .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 As an additional hint in favor of the idea that such agents mediate their effects through the immune system, it appears that combinations of ICD inducers with ICIs are particularly efficient at the clinical level. 25,26 Schematically, the immunogenicity conferred by ICD requires the combination of two major features, (i) antigenicity and (ii) adjuvanticity. 27 With respect to antigenicity, cancer cells differ from their normal counterparts in their antigenic makeup including the immunopeptidome, that is, the sum of antigenic peptides bound to MHC Class I molecules on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin, a second-generation anticancer drug used in the treatment of gastric cancer, has shown a comparable or even better therapeutic effect compared to cisplatin. Studies have shown that this partly depends on co-inducing ICD, which stimulates an effective antitumor immune response [11]. Herein, we constructed an ICD-based risk model and nomogram using bioinformatic methods, which accurately predicts the prognosis of patients with gastric cancer, providing a foundation for studying the mechanism of ICD in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%